Microbiological assessment of wastewater of industrial enterprises in Kyiv and the Kyiv region (Environment & Health, 2024)
The aim: industrial wastewater microbiological monitoring and its effect on the drainage water condition.Purpose: microbiological monitoring of industrial wastewater and its impact on the state of surface waters.Materials and methods: wastewater quality evaluation was performed according to the parameters: the lactose-positive coliforms (LPC) count, the coli index, coliphages count and the pathogenic enterobacteria presence.Results: wastewater (WW) treated with full biological treatment and disinfection, UV radiation, chlorination and the cleansing structures use was studied. Industrial WW samples met the 1-2 quality class requirements.7 food processing wastewater samples did not meet the discharge into an open water requirements in terms of LCP count, which was in the range from 2300 CFU/dm3 to 46000 CFU/dm3, it indicates water fecal pollution. At the same time, according to the coliphages count, these samples belonged to the 2nd quality class.Surface water samples comparative analysis before and after the industrial wastewater discharge shows that the investigated wastewater discharge did not lead to surface watercourse microbiological contamination.Conclusions: according to the 41 industrial wastewater reuse samples microbiological quality monitoring results for the period January 2021-June 2023, 34 WW samples were met the 1-2 quality class requirements, which indicates their satisfactory purification and the discharge possibility into an open water body. 7 samples did not meet the LCP number requirement, which indicates poor-quality purification and their fecal contamination.It was established that the surface watercourse before and after the reuse wastewater discharge, according to the LCP count, the coli index, coliphages count belong to the 1-2 quality class. The investigated industrial wastewater discharge did not exceed the allowance allocation and did not lead to surface waters microbiological contamination.
Keywords: wastewater; lactose-positive coliforms; coliphages